Synthesis of polyesters by an efficient heterogeneous phosphazene (P1)-Porous Polymeric Aromatic Framework catalyzed-Ring Opening Polymerization of lactones. (October 2017) - Liras, Marta; Verde-Sesto, Ester; Iglesias, Marta; Sánchez, Félix
Graphical abstract: Highlights: The postfunctionalization of PPAF with phophazene (P1) group has been described. The postfunctionalization degree and porosity has been controlled. The new materials are an efficient heterogeneous catalyst of ROP of Lactones. This is the first example of a porous polymer used as ROP catalyst. Abstract: A novel phosphazene superbase (P1) organocatalyst heterogenized on a Porous Polymeric Aromatic Framework (PPAF) based on an adamantine node catalyzed metal-free ring-opening polymerization (ROP) of lactones to yield polyesters, showing a 7.7-fold increase in the turnover number for δ -valerolactone ( δ -VL) and 3.3-fold increase in the case of ε -caprolactone ( ε -CL) as comparing with its soluble counterpart. The heterogeneous catalyst can be reused until four times without loss of activity.